Boal, Brecht's reader: a question of method - Zanetti, Anderson [UNESP] (Univ Sao Paulo, Escola Comunicacoes & Artes, 2018)
This paper approaches Hegel and Brecht: the character as subject or the character as object?, the most important essay written by Augusto Boal on Bertolt Brecht's poetics. The objective is to emphasize that Boal's limits of interpretation reside on the absence of discussion about the role of dialectical materialism in Brecht's work. Therefore, the range of Boal's reading would not overcome the formal scope of literary criticism.
Keywords: Augusto Boal; Bertolt Brecht; Method; Dialectical materialism